Interpretation of architectural meanings of post-independence Malaysian buildings through semiotic approach / Azlaini Abdul Aziz - Abdul Aziz, Azlaini (2021)
The architectural identity of Malaysian is insignificant today. They were highly being misinterpreted and misunderstood. Crucial issues concerning their projections have escalated, particularly in the 1980’s on wards. This situation has caused concerns to both Malaysian government and building professionals. Several congresses, seminars and important national policies were introduced to confront these issues. However, the outcomes had not been observable till this day. This study aims to investigate the success level on employment of signs and symbols in post-independence Malaysian architecture. The objectives are to interpret the characteristics, orientations and cultural emphasis in projecting identity and meaning through architecture. The semiotic approach was employed in the study. The structure produced through the interpretation helps affirm the consistency of intrinsic meanings projected by the selected buildings. Fourteen post-independence public buildings were selected as the subject for case study. They are classified under four categories of architectural genre known as Malaysian Vernacular Revivalism, Interpretive Islamic Symbolism, Tropical Architecture and Modernistic Expressionism, which are used as determinants of design patterns. It is to ensure consistencies in observing the use of signs and symbols within the architecture, built after the early iconic Malaysian architecture during the 1960’s. A three-stage process was carried out in the analysis. The first stage investigates the use of shapes and lines (SLA) in architectural compositions. The second examines the visual composition and perception (VCPA) criteria in design. The visual communication technique was employed for the first two steps in interpreting meaning on both pre- and postindependence Malaysian architecture, in order to gauge the similarities and differences in their designs. The final stage involves a “Semiotic Structural Analysis” (SSA) on Post-Independence Malaysian architecture. The method was based on the technique introduced by San Jose State University, California which was widely used in interpreting meaning from design objects. The so-called “first impression counts” visual assessment technique was employed during the observation research process to obtain instant impression and level of expectations on chosen building designs. The finding of the study shows that the signs and symbols projected by the post-independence architecture was inappropriately used and have not been effectively employed to portray what can been considered as the “national identity”. The local culture and characteristics of Malaysia have not been visible as anticipated. This major contribution of the study is the use of semiotics as a potent technique in decoding intrinsic meaning of objects and buildings. Consequently, further research can be done by using the technique in framing a more perceptive and responsive Malaysian architecture.